Development of Mobile Application for Health and Fitness Guidance - FIT DAY - Yap, Sue Shan; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2022)
FIT DAY is an Android-based mobile application to guide people to do workouts and pay attention to their food calorie intakes to maintain their fitness. The main objective of the FIT DAY application is to boost potential users to be more health concerns. This application consists of five modules: Food Calories, Exercise, Body Mass Index (BMI), Step Counter, and Reminder. Most of the current health and fitness application focused on the workout part compared to the food calories part. Therefore, the Agile methodology supports the project’s development through its five(5) phases. The development of FIT DAY application in Android Studio, and Firebase Database enables its implementation in an Android-based platform. Ten respondents aged between 18 to 40 years old participated in the user acceptance testing. Technology Acceptance Model (TAM) model utilized for user testing shows positive acceptance in the aspects of interface, content, and functional features of the FIT DAY application. Overall, this application enables users to track daily calories intake and acquire health and fitness methods.